The Role of Body Language Inside the Language Classroom (Journal of Pedagogical Inventions and Practices, 2023)
As we know, body language, an inseparable part of nonverbal communication, plays an important role in foreign language learning and teaching. Language teachers use body language in interpersonal communication in the classroom for a wide variety of reasons. This article investigates some of the reasons why language teachers use body language in the foreign language classroom.